2012
DOI: 10.1186/1748-717x-7-91
|View full text |Cite
|
Sign up to set email alerts
|

MUC5B levels in submandibular gland saliva of patients treated with radiotherapy for head-and-neck cancer: A pilot study

Abstract: BackgroundThe salivary mucin MUC5B, present in (sero)mucous secretions including submandibular gland (SMG) saliva, plays an important role in the lubrication of the oral mucosa and is thought to be related to the feeling of dry mouth. We investigated if MUC5B levels in SMG saliva could distinguish between the presence or absence of severe dry mouth complaints 12 months after radiotherapy (RT) for head-and-neck cancer (HNC).FindingsTwenty-nine HNC patients with a residual stimulated SMG secretion rate of ≥0.2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
6
25
0
Order By: Relevance
“…MUC5B plays an important role in the many functions of saliva [15]. Changes in MUC5B concentration have been associated with the appearance of xerostomia in patients subjected to radiotherapy of the head and neck [16] and in patients with Sjögren's syndrome [17]. The present results concur with research previously published by our research team that related the presence of xerostomia to poor clinical management of asthma and high IC use [18].…”
Section: Discussionsupporting
confidence: 94%
“…MUC5B plays an important role in the many functions of saliva [15]. Changes in MUC5B concentration have been associated with the appearance of xerostomia in patients subjected to radiotherapy of the head and neck [16] and in patients with Sjögren's syndrome [17]. The present results concur with research previously published by our research team that related the presence of xerostomia to poor clinical management of asthma and high IC use [18].…”
Section: Discussionsupporting
confidence: 94%
“…Xerostomia measures are reported in three studies (Dijkema et al., ; Randall et al., ; Tiwana et al., ). No studies have undertaken an analysis for a possible relationship between individual saliva components, and physician‐reported (Tiwana et al., ) or patient‐reported (Dijkema et al., ; Randall et al., ) xerostomia scores. We assessed for a possible relationship between PG saliva analytes and xerostomia severity after IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, a pilot study on 29 patients who had received radiotherapy for head-and-neck cancer showed that the 12 patients with mild or no xerostomia had higher levels of MUC5B in their submandibular saliva than the 17 patients with more severe xerostomia. 31 Thus MUC5B may help to reduce the subjective sensation of xerostomia (dry mouth). However, Yakubov 32 has pointed out that no single component is able to explain the lubricating ability of saliva and that it is likely to be due to a combination of mucins, glycosylated proline-rich proteins and some lower molecular weight proteins.…”
Section: Moistening and Lubricationmentioning
confidence: 99%